Basic Personal Values and the Meaning of Left-Right Political Orientations in 20 Countries - Piurko, Yuval; Schwartz, Shalom H.; Davidov, Eldad (Political psychology, 2011)
This study used basic personal values to elucidate the motivational meanings of "left" and "right" political orientations in 20 representative national samples from the European Social Survey (2002-2003). It also compared the importance of personal values and sociodemographic variables as determinants of political orientation. Hypotheses drew on the different histories, prevailing culture, and socioeconomic level of three sets of countries—liberal, traditional, and postcommunist. As hypothesized, universalism and benevolence values explained a left orientation in both liberal and traditional countries and conformity and tradition values explained a right orientation; values had little explanatory power in postcommunist countries. Values predicted political orientation more strongly than sociodemographic variables in liberal countries, more weakly in postcommunist countries, and about equally in traditional countries.